P009: Improving elderly care transitions through the local adaptation and implementation of the Acute Care for Elderly (ACE) program. (15th May 2017) - Archambault, P.M.; Vaillancourt, H.; Drouin, V.; Dupuis, A.; McGinn, C.; Rivard, J.; Bernier, L.; Savard, A.; Girouard, C.; Poiré, M.; Gilbert, J.; Kroon, C.; et al.
Abstract : Introduction: Decreasing readmission rates and return emergency department (ED) visits represent a major challenge for health organizations. Seniors are especially vulnerable to discharge adverse events which can result in unplanned readmissions and loss of physical, functional and/or cognitive capacity. The ACE Collaborative is a national quality improvement initiative that aims to improve care of elderly patients. We aimed to adapt Mount Sinai's Care Transitions program to our local context in order to decrease avoidable readmissions and ED visits among seniors.Methods: We performed a prospective pre/post implementation cohort study. We recruited frail elderly hospitalized patients (≥50 years old) discharged to home and at risk of readmission (modified LACE index score≥7/12). We excluded patients being discharged to long-term nursing homes or institutions. Our intervention is based on selected strategic ACE Care Transitions best practices: transition coach, telehealth personal response services and a structured discharge checklist. The intervention is offered to selected patients before hospital discharge. Our primary outcome is a 30-day post-discharge composite of hospital readmission and return ED visit rate. Our secondary outcomes are functional autonomy, satisfaction with care transition, quality of life, caregiver strain and healthcare resource use at recruitment and at 30-days follow-up. Hospital-level administrative data is also collected to measure global effect of practice changes.Results: The project is currently ongoing and preliminary results are available for the pre-implementation cohort only. Patients in this cohort (n=33) were mainly men (61%), aged 75±10 years and presented an OARS score (Activities of Daily Living instrument that ranges from 0-28) of 5.6±4.9. At 30 days post-discharge, the patients in our cohort had a 42.4% readmission rate (14 hospitalisations) and a 54.5% return ED visit rate (18 visits). For the same time period, readmission and return ED rates for all patients in the same corresponding age-group at the hospital level were 14.4% and 21.9%, respectively. Further results for our post-intervention cohort will be presented at CAEP 2017.Conclusion: Our cohort of elderly patients have high readmission and return ED visit rates. Our ongoing quality improvement project aims to decrease these readmissions and ED visits.